Novel white light emitting phosphate fluorescent glass ceramic for WLED (White Light Emitting Diode) and preparation method of novel white light emitting phosphate fluorescent glass ceramic

Through the use of 10Bao-32ZNO-32P2O5-26B2O3-phosphate glass ceramic materials with doped TM3+, TB3+and SM3+in WLED materials, the existing WLED material color temperature and aging packaging material are solved, and high fluorescent quantum efficiency and closeness are close to The light emitting effect of the white light.

CN119330599APending Publication Date: 2025-01-21XINJIANG TECH INST OF PHYSICS & CHEM CHINESE ACAD OF SCI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411465366.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing WLED materials lack red emission, low color temperature, damage to the human eye, and aging of the packaging material leads to a decrease in luminous efficiency.

Method used

Using 10Bao-32ZNO-32P2O5-26B2O3, phosphate glass ceramic materials, multi-phase complexes are obtained through glass control temperature crystals, mixed with TM3+, TB3+, and SM3+ions. It has high fluorescent quantum efficiency and close to the positive white light through specific thermal treatment steps. Materials with glowing color.

Benefits of technology

With the inspiration of the 363nm light source, the color temperature changed from cold white to neutral light. The fluorescent quantum efficiency increased from 19.37 % to 27.85 %.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330599A_ABST
    Figure CN119330599A_ABST
Patent Text Reader

Abstract

The invention relates to a phosphate fluorescent glass ceramic material for white light emission of a WLED (White Light Emitting Diode) and a preparation method of the phosphate fluorescent glass ceramic material, the glass general formula of the glass ceramic is 10BaO-32ZnO-32P2O5-26B2O3 (mol%), and the phosphate fluorescent glass ceramic material is prepared by the steps of raw material preparation, melting and quenching, internal stress elimination, cutting and polishing and heat treatment. According to the glass ceramic material, a multi-phase compound in which a glass phase and a microcrystalline phase coexist is obtained through glass temperature control crystallization, the main body characteristic of the glass phase is reserved, and the optical characteristic of the microcrystalline phase is also reserved. The glass phase provides a stable matrix environment, high-strength mechanical properties and macroscopic morphology plasticity for the microcrystalline phase. The fluorescent material has a light-emitting color close to pure white light and relatively high fluorescence quantum efficiency, and can be used as a novel white light-emitting fluorescent material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of phosphate fluorescent glass ceramics, and in particular to a white light emitting phosphate fluorescent glass ceramic material for WLED and a preparation method thereof. Background Art

[0002] With the development of science and technology, human lighting sources have evolved from incandescent lamps, fluorescent lamps and gas discharge lamps to the fourth generation of lighting technology today - white light emitting diodes (WLED). As a new type of solid-state lighting source, WLED has excellent properties such as energy saving, environmental protection, long life and small size. It plays a vital role in applications such as backlight, car lights and daily lighting. The current method to realize WLED is mainly to combine blue light LED chips with phosphors. The most classic combination of this method is to combine blue light InGaN chips with yellow phosphor Y3Al5O 12 :Ce 3+ (YAG:Ce), which is also the most mature commercial WLED at present, but this method lacks red light emission and has a low color temperature. As a lighting source, it will cause certain damage to the human eye, and its stability also needs to be further improved. In addition, epoxy resin is often used as a packaging material in the WLED packaging process. This material will age and turn yellow after long-term use, resulting in a significant decrease in luminous efficiency. Rare earth-doped phosphate glass ceramics can better avoid the above problems. Phosphate glass has lower phonon energy, reduces the occurrence of non-radiative relaxation, and improves luminous efficiency. Compared with epoxy resin encapsulated WLEDs, WLEDs composed of rare earth-doped glass ceramics do not require encapsulation, have less energy loss, good stability, and better performance in extreme environments. Therefore, rare earth-doped phosphate glass ceramics have great potential to replace traditional phosphors as white light sources. Summary of the invention

[0003] The purpose of the present invention is to provide a novel white light emitting phosphate fluorescent glass ceramic for WLED and a preparation method thereof. The glass ceramic has a general chemical formula of 10BaO-32ZnO-32P2O5-26B2O3 (mol%) and is prepared by raw material preparation, melting and quenching, eliminating internal stress, cutting and polishing, and heat treatment steps. The glass ceramic material is a multiphase composite of coexistence of glass phase and microcrystalline phase obtained by glass temperature controlled crystallization, which retains both the main characteristics of the glass phase and the optical characteristics of the microcrystalline phase. The glass phase provides a stable matrix environment, high-strength mechanical properties and macroscopic morphology plasticity for the microcrystalline phase. It has a luminous color close to that of positive white light and a high fluorescence quantum efficiency, and can be used as a novel white light emitting fluorescent material.

[0004] The invention discloses a novel white light emitting phosphate fluorescent glass ceramic for WLED. The glass substrate of the phosphate fluorescent glass ceramic is 10BaO-32ZnO-32P2O5-26B2O3, which is composed of BaCO3 10%-15%, ZnO 15%-20%, NH4H2PO4 45%-50%, H3BO3 20%-25% by mass percentage. Tm is doped in the form of oxide in the glass substrate. 3+ , Tb 3+ and Sm 3+ , wherein the doped Tm2O3, Tb4O7 and Sm2O3 account for 0.2%-0.3% of the total mass of the raw materials, 0.9%-1% of Tb4O7 and 0.9%-1% of Sm2O3, respectively. The specific operation is carried out according to the following steps:

[0005] a. Raw material preparation: weigh the raw materials BaCO3 10%-15%, ZnO 15%-20%, NH4H2PO4 45%-50%, H3BO3 20%-25%, Tm2O3 0.2%-0.3%, Tb4O7 0.9%-1%, Sm2O3 0.9%-1% by mass, put them in an agate mortar and grind them thoroughly to obtain a mixture, and then transfer the mixture to a corundum crucible;

[0006] b. Melting and quenching: placing the corundum crucible containing the mixture in step a in a muffle furnace at a temperature of 1200-1300°C, calcining for 2-4 hours, pouring the high-temperature melt onto the surface of a preheated steel plate for quenching to obtain glass; wherein the steel plate needs to be preheated in a muffle furnace in advance, the furnace temperature rises to 400-500°C, and the preheating time is 5-10 minutes;

[0007] c. Eliminating internal stress: Immediately placing the glass quenched in step b in a muffle furnace for heat treatment to eliminate internal stress, and naturally cooling to room temperature to obtain glass;

[0008] d. Cutting and polishing: cutting and polishing the glass obtained in step c to obtain a glass block;

[0009] e. Heat treatment: The glass block obtained in step d is placed in a muffle furnace for heat treatment to obtain a phosphate fluorescent glass ceramic sheet.

[0010] A method for preparing a novel white light emitting phosphate fluorescent glass ceramic for WLED is carried out according to the following steps:

[0011] a. Raw material preparation: weigh the raw materials BaCO3 10%-15%, ZnO 15%-20%, NH4H2PO4 45%-50%, H3BO3 20%-25%, Tm2O3 0.2%-0.3%, Tb4O7 0.9%-1%, Sm2O3 0.9%-1% by mass, put them in an agate mortar and grind them thoroughly to obtain a mixture, and then transfer the mixture to a corundum crucible;

[0012] b. Melting and quenching: placing the corundum crucible containing the mixture in step a in a muffle furnace at a temperature of 1200-1300° C., calcining for 2-4 hours, pouring the high-temperature melt onto the surface of a preheated steel plate for quenching to obtain glass;

[0013] c. Eliminating internal stress: Immediately place the glass quenched in step b in a muffle furnace and heat it to 400-500°C for 5-6 hours to eliminate internal stress by heat treatment, and then naturally cool it to room temperature to obtain glass;

[0014] d. Cutting and polishing: cutting and polishing the glass obtained in step c to obtain a glass block;

[0015] e. Heat treatment: placing the glass block obtained in step d in a muffle furnace and raising the furnace temperature to 550-600° C. for 0-2 h for heat treatment and naturally cooling to room temperature to obtain a phosphate fluorescent glass ceramic sheet having a color coordinate changing from cold white light to neutral light under the excitation of a 363 nm light source, a color temperature of 5053 K-6581 K, and a fluorescence quantum efficiency of 19.37%-27.85%.

[0016] The steel plate in step b needs to be preheated in a muffle furnace in advance, with the furnace temperature rising to 400-500° C. and the preheating time being 5-10 minutes.

[0017] The novel white light emitting phosphate fluorescent glass ceramic for WLED and its preparation method described in the present invention have low phonon energy, can carry a high concentration of rare earth ions, have better stability than traditional WLED materials that need to be encapsulated, and can reduce the problem of reduced luminous efficiency caused by aging of encapsulation materials. Therefore, the fluorescent glass ceramic material of the present invention can be used as a novel white light emitting material for WLED.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The color coordinates of BaO-ZnO-P2O5-B2O3 glass-ceramics co-doped with Tm2O3 / Tb4O7 / Sm2O3 at the optimal heat treatment time are (0.3248, 0.3483), which is a typical neutral white light emission color and is closest to the positive white light color coordinates (0.3333, 0.3333);

[0020] (2) With the increase of heat treatment time, the luminescence color of Tm2O3 / Tb4O7 / Sm2O3 co-doped BaO-ZnO-P2O5-B2O3 glass and glass ceramics gradually changes from cold white light to neutral white light, and the emission intensity is effectively enhanced;

[0021] (3) With the increase of heat treatment time, the fluorescence quantum efficiency of Tm2O3 / Tb4O7 / Sm2O3 co-doped BaO-ZnO-P2O5-B2O3 glass and glass ceramics increased from 19.37% to 27.85%. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is the emission spectrum of the phosphate fluorescent glass ceramics in Examples 1, 2, 3, and 4 of the present invention;

[0023] Figure 2 are the emission spectrum color coordinates of the phosphate fluorescent glass ceramics in Examples 1, 2, 3, and 4 of the present invention;

[0024] Figure 3 It is the fluorescence quantum efficiency of the phosphate fluorescent glass ceramics in Examples 1, 2, 3 and 4 of the present invention. DETAILED DESCRIPTION

[0025] Example 1

[0026] a. Raw material preparation: weigh the raw materials BaCO3 12.6%, ZnO 16.9%, NH4H2PO4 47.7%, H3BO3 20.7%, Tm2O3 0.25%, Tb4O7 0.96%, Sm2O3 0.89% by mass, put them in an agate mortar and grind them thoroughly to obtain a mixture, and then transfer the mixture to a corundum crucible;

[0027] b. Melting and quenching: placing the corundum crucible containing the raw material mixture in step a in a muffle furnace at a temperature of 1300°C, calcining for 2 hours, pouring the high-temperature melt onto the surface of a preheated steel plate for quenching. The steel plate needs to be preheated at 450°C for 5 minutes in advance to obtain glass;

[0028] c. Eliminating internal stress: placing the glass obtained in step b in a muffle furnace at a temperature of 420° C. for 5 hours to perform heat treatment to eliminate internal stress, and then naturally cooling to room temperature to obtain glass;

[0029] d. Cutting and polishing: Cut and polish the glass obtained in step c to obtain a Tm2O3 / Tb4O7 / Sm2O3 co-doped BaO-ZnO-P2O5-B2O3 glass sheet.

[0030] The optical test of Tm2O3 / Tb4O7 / Sm2O3 co-doped BaO-ZnO-P2O5-B2O3 glass material was carried out, and the emission spectrum was obtained under the excitation of 363nm light source. Figure 1 As shown, the color coordinates (0.3108, 0.3325) are Figure 2 As shown, after calculation, the color temperature is 6581K and the fluorescence quantum efficiency is 19.37%.

[0031] Example 2

[0032] a. Raw material preparation: weigh the raw materials BaCO3 12.6%, ZnO 16.9%, NH4H2PO4 47.7%, H3BO3 20.7%, Tm2O3 0.25%, Tb4O7 0.96%, Sm2O3 0.89% by mass, put them in an agate mortar and grind them thoroughly to obtain a mixture, and then transfer the mixture to a corundum crucible;

[0033] b. Melting and quenching: placing the corundum crucible containing the raw material mixture in step a in a muffle furnace at a temperature of 1300°C for calcination for 2 hours, and then pouring the high-temperature melt onto the surface of a preheated steel plate for quenching. The steel plate needs to be preheated at 450°C for 5 minutes in advance to obtain glass;

[0034] c. Eliminating internal stress: placing the glass obtained in step b in a muffle furnace at a temperature of 450° C. for 5.5 hours to perform heat treatment to eliminate internal stress, and then naturally cooling to room temperature to obtain glass;

[0035] d. Cutting and polishing: cutting and polishing the glass obtained in step c to obtain a glass block;

[0036] e. Heat treatment: Place the glass block obtained in step d in a muffle furnace, keep it at 585° C. for 1 hour, and then cool it naturally to room temperature to obtain a Tm2O3 / Tb4O7 / Sm2O3 co-doped BaO-ZnO-P2O5-B2O3 phosphate fluorescent glass ceramic sheet.

[0037] Optical testing of Tm2O3 / Tb4O7 / Sm2O3 co-doped BaO-ZnO-P2O5-B2O3 glass-ceramic materials yielded emission spectra such as Figure 1 As shown, the color coordinates (0.3124, 0.336) are Figure 2 As shown, after calculation, the color temperature is 6472K and the fluorescence quantum efficiency is 19.75%.

[0038] Example 3

[0039] a. Raw material preparation: weigh the raw materials BaCO3 12.6%, ZnO 16.9%, NH4H2PO4 47.7%, H3BO3 20.7%, Tm2O3 0.25%, Tb4O7 0.96%, Sm2O3 0.89% by mass, put them in an agate mortar and grind them thoroughly to obtain a mixture, and then transfer the mixture to a corundum crucible;

[0040] b. Melting and quenching: placing the corundum crucible containing the raw material mixture in step a in a muffle furnace at a temperature of 1200° C. and calcining for 3 hours, then pouring the high-temperature melt onto the surface of a preheated steel plate for quenching. The steel plate needs to be preheated at a temperature of 400° C. for 10 minutes in advance to obtain glass;

[0041] c. Eliminating internal stress: placing the glass obtained in step b in a muffle furnace at a temperature of 400° C. for 5 hours to perform heat treatment to eliminate internal stress, and then naturally cooling to room temperature to obtain glass;

[0042] d. Cutting and polishing: cutting and polishing the glass obtained in step c to obtain a glass block;

[0043] e. Heat treatment: Place the glass block obtained in step d in a muffle furnace and heat it to 585°C for 1.5 hours for heat treatment, and cool it naturally to room temperature to obtain a Tm2O3 / Tb4O7 / Sm2O3 co-doped BaO-ZnO-P2O5-B2O3 phosphate fluorescent glass ceramic sheet.

[0044] The optical test of BaO-ZnO-P2O5-B2O3 glass ceramic material co-doped with Tm2O3 / Tb4O7 / Sm2O3 was carried out, and the emission spectrum was obtained under the excitation of 363nm light source. Figure 1 As shown, the color coordinates (0.3248, 0.3483) are Figure 2 As shown, after calculation, the color temperature is 5830K and the fluorescence quantum efficiency is 22.72%.

[0045] Example 4

[0046] a. Raw material preparation: weigh the raw materials BaCO3 12.6%, ZnO 16.9%, NH4H2PO4 47.7%, H3BO3 20.7%, Tm2O3 0.25%, Tb4O7 0.96%, Sm2O3 0.89% by mass, put them in an agate mortar and grind them thoroughly to obtain a mixture, and then transfer the mixture to a corundum crucible;

[0047] b. Melting and quenching: placing the corundum crucible containing the raw material mixture in step a in a muffle furnace at a temperature of 1250° C. for calcination for 3 hours, and then pouring the high-temperature melt onto the surface of a preheated steel plate for quenching. The steel plate needs to be preheated at 500° C. for 8 minutes in advance to obtain glass;

[0048] c. Eliminating internal stress: placing the glass obtained in step b in a muffle furnace at a temperature of 500° C. for 6 hours to perform heat treatment to eliminate internal stress, and then naturally cooling to room temperature to obtain glass;

[0049] d. Cutting and polishing: cutting and polishing the glass obtained in step c to obtain a glass block;

[0050] e. Heat treatment: Place the glass block obtained in step d in a muffle furnace, keep it at 600°C for 2 hours, and cool it naturally to room temperature to obtain a Tm2O3 / Tb4O7 / Sm2O3 co-doped BaO-ZnO-P2O5-B2O3 phosphate fluorescent glass ceramic sheet.

[0051] The optical test of BaO-ZnO-P2O5-B2O3 phosphate fluorescent glass ceramic material co-doped with Tm2O3 / Tb4O7 / Sm2O3 was carried out. The emission spectrum was obtained under the excitation of 363nm light source. Figure 1 As shown, the color coordinates (0.3454, 0.3745) are Figure 2 As shown, after calculation, the color temperature is 5053K and the fluorescence quantum efficiency is 27.85%.

Claims

1. A phosphate fluorescent glass ceramic for white light emission of WLED, characterized in that: The chemical formula of the glass substrate of the phosphate fluorescent glass ceramic is 10BaO-32ZnO-32P2O5-26B2O3, which is composed of BaCO3 10%-15%, ZnO 15%-20%, NH4H2PO4 45%-50%, H3BO3 20%-25% by mass percentage. Tm is doped in the form of oxide. 3 + , Tb 3+ and Sm 3+ , wherein the doped Tm2O3, Tb4O7 and Sm2O3 account for 0.2%-0.3% of the total mass of the raw materials, 0.9%-1% of Tb4O7 and 0.9%-1% of Sm2O3, respectively. The specific operation is carried out in the following steps: a. Raw material preparation: weigh the raw materials BaCO3 10%-15%, ZnO 15%-20%, NH4H2PO4 45%-50%, H3BO3 20%-25%, Tm2O3 0.2%-0.3%, Tb4O7 0.9%-1%, Sm2O3 0.9%-1% by mass percentage, put them in an agate mortar and grind them thoroughly to obtain a mixture, and then transfer the mixture to a corundum crucible; b. Melting and quenching: placing the corundum crucible containing the mixture in step a in a muffle furnace at a temperature of 1200-1300°C, calcining for 2-4 hours, pouring the high-temperature melt onto the surface of a preheated steel plate for quenching to obtain glass; wherein the steel plate needs to be preheated in a muffle furnace in advance, the furnace temperature rises to 400-500°C, and the preheating time is 5-10 minutes; c. Eliminating internal stress: Immediately placing the glass quenched in step b in a muffle furnace for heat treatment to eliminate internal stress, and naturally cooling to room temperature to obtain glass; d. Cutting and polishing: cutting and polishing the glass obtained in step c to obtain a glass block; e. Heat treatment: The glass block obtained in step d is placed in a muffle furnace for heat treatment to obtain a phosphate fluorescent glass ceramic sheet.

2. A method for preparing a novel white light emitting phosphate fluorescent glass ceramic for WLED, characterized in that: Follow these steps: a. Raw material preparation: weigh the raw materials BaCO3 10%-15%, ZnO 15%-20%, NH4H2PO4 45%-50%, H3BO3 20%-25%, Tm2O3 0.2%-0.3%, Tb4O7 0.9%-1%, Sm2O3 0.9%-1% by mass percentage, put them in an agate mortar and grind them thoroughly to obtain a mixture, and then transfer the mixture to a corundum crucible; b. Melting and quenching: placing the corundum crucible containing the mixture in step a in a muffle furnace at a temperature of 1200-1300° C., calcining for 2-4 hours, pouring the high-temperature melt onto the surface of a preheated steel plate for quenching to obtain glass; c. Eliminating internal stress: Immediately place the glass quenched in step b in a muffle furnace and heat it to 400-500°C for 5-6 hours to eliminate internal stress by heat treatment, and then naturally cool it to room temperature to obtain glass; d. Cutting and polishing: cutting and polishing the glass obtained in step c to obtain a glass block; e. Heat treatment: placing the glass block obtained in step d in a muffle furnace and raising the furnace temperature to 550-600° C. for 0-2 h for heat treatment, and naturally cooling to room temperature to obtain a phosphate fluorescent glass ceramic sheet having a color coordinate changing from cold white light to neutral light under excitation of a 363 nm light source, a color temperature of 5053 K-6581 K, and a fluorescence quantum efficiency of 19.37%-27.85%.

3. The method for preparing the novel white light emitting phosphate fluorescent glass ceramic for WLED according to claim 2, characterized in that: The steel plate in step b needs to be preheated in a muffle furnace in advance, with the furnace temperature rising to 400-500° C. and the preheating time being 5-10 minutes.

Citation Information

Cited By

  • Novel yellow orange light-emitting phosphate glass ceramic material and preparation method thereof

    CN119390353A